Anterior Implant Placement with Block Graft for Ridge Augmentation in a Young Patient with Severe Bone Deficiency: A Clinical Case Report - Mistry, Gaurang; Kini, Ashwini; Mehta, Kunal; Singh, Sapna; Ansari, Rasha; Gujar, Yash (Journal of Neonatal Surgery, 2025)
The present case report describes the successful rehabilitation of a young patient with a missing anterior tooth and severe bone resorption using a combination of block grafting and dental implant placement. A young adult male had a missing maxillary central incisor for 12 years, leading to significant bone loss in the region. A block graft was harvested from the mandibular symphysis and used for ridge augmentation, followed by implant placement with immediate loading of a temporary crown. The graft successfully restored both vertical and horizontal dimensions of the ridge, creating an optimal environment for implant osseointegration. A final prosthesis was placed after a healing period of three months, providing both functional and esthetic restoration. The case report highlights the effectiveness of autogenous block grafting combined with guided bone regeneration as a reliable and predictable method for managing severe bone deficiency in implant dentistry